Odpowiedzi

Najlepsza Odpowiedź!
2009-12-04T19:55:04+01:00
2x-5 x-6 x+y
..2..-..4.=..2.. / wszystko ×4
3x-1 2y-5 2x+4
..10.+.5..=..2.. / wszystko ×10

2(2x-5)-x-6=2(x+y)
3x-1+2(2y-5)=5(2x+y)

4x-10-x-6=2x+2y / -2x
3x-1+4y-10=10x+5y

x-16=2y / +16
3x+4y-11=10x+5y / -5y

x=2y+16
3x-y-11=10x / -3x

x=2y+16
-y-11=7x

x=2y+16
-y-11=7(2y+16)

x=2y+16
-y-11=14y+112 / +11

x=2y+16
-y=14y+123 / -14y

x=2y+16
-15y=123 / :(-15)

x=2y+16
y=(-8.2)

x=2×(-8.2)+16
y=(-8.2)

x=(-16.4)+16
y=(-8.2)

x=(-0.4)
y+(-8.2)